(untitled) (International Journal of Physiotherapy, 2016)
Background: Periarthritis or Adhesive shoulder occurs among 7-21% of the population, which was characterized by traumatic stiff shoulders in both active and passive range of actions. The aim of the study was to compare the efficacy between Muscle energy technique (MET) and Mobilization technique (MT) coupled with ultrasound therapy in reduction of pain and increasing functional ability of subjects with adhesive shoulder. Methods: 30 subjects were randomly assigned for the experimental study by the selection criteria and divided into 2 groups: Group A -Muscle energy technique with ultrasound therapy (METU) and Group B- Mobilization technique with ultrasound therapy (MTU). The period of intervention was 5 sessions per week for 21 days. The therapy progress was evaluated by VAS and SPADI scores pre and post every 7 days of therapy. Results: The analysis was non-blind randomized experimental study for the subjects with adhesive shoulders. Both the treatment groups showed improvement comparing pre and post treatment, while Group A showed significant difference compared to Group B in pain relief and functional abilities. Statistically comparing the mean values of SPADI of the two treatment groups has indicated METU (28.93) as more efficient than MTU (36.80) at P≤ 0.001. Conclusion: The current study has concluded that the muscle energy technique coupled with ultrasound therapy imparts more effective solution than the mobilization technique coupled with ultrasound. Hence, this study has demonstrated a better combination therapy regimen for the treatment of periarthritic shoulder the physiotherapists. Similarly, potential of this combination therapy can be explored on other types of ailments demanding physiotherapy.